Georgian folk-fusion through the lens of cultural and economic values - Lomsadze Teona (Muzikologija)
This article examines the cultural and economic value concepts of folkfusion music in Georgia, a genre that blends local traditional (folk and sacred) music with Western popular styles. The focus is on exploring how the tension between perceiving traditional music as cultural heritage and as an economic commodity affects the development of folk-fusion. The study highlights the genre’s potential to serve as a cultural ambassador for Georgia internationally, while also noting the current lack of consistent support for its strengthening and consolidation. The article argues that achieving a balance between cultural embeddedness and economic sustainability is crucial for the genre’s development and integration into the global music industry. It concludes that realizing the potential of folk-fusion requires shifts in attitudes among musicians, audiences, and policymakers, along with increased institutional support.